Pendidikan Kewarganegaraan Berbasis Multikultural Dalam Penguatan Sikap Toleransi Siswa SMA - Kamlasi, Anjulin Yonathan; Kusdarini, Eny (Universitas Negeri Malang, 2022)
This study aims to describe the urgency and implementation of multicultural-based citizenship education in strengthening the tolerance attitude of students. This study uses a qualitative method with a case study type of research. The determination of the subject was carried out using a purposive sampling technique, namely students from SMA Negeri 2 Kupang. Data collection was carried out through interviews, observation, and documentation techniques. Data were analyzed using an interactive model from Miles and Huberman including data collection, data reduction, data presentation, and conclusions. The results of the study show that the urgency of multicultural-based Citizenship Education can provide students with an understanding of diversity so as to strengthen their tolerance towards others. Multicultural-based Citizenship Education in strengthening the tolerance attitude of Kupang 2 Public High School students is carried out through two forms of activities, namely learning in the classroom by providing material by teachers that is integrated with the values of diversity and learning outside the classroom through religious activities, cultural competition, extracurriculars, and other activities.